When Executives Pledge Integrity: The Effect of the Accountant’s Oath on Firms’ Financial Reporting - Heese, Jonas; Pérez-Cavazos, Gerardo; Peter, Caspar David (The Accounting Review, 2023)
ABSTRACT We study the effect of executives’ pledges of integrity on firms’ financial reporting outcomes by exploiting a 2016 regulation that requires holders of Dutch professional accounting degrees to pledge an integrity oath. We identify chief executive officers (CEOs) and chief financial officers (CFOs) required to take the integrity oath and find that firms reduce income-increasing discretionary accruals after executives took the oath. These firms also reduce discretionary expenditures, indicating that oath-taking executives reduce overall earnings management and do not merely substitute accruals-based with real-activities earnings management. These effects are concentrated in firms where the CFO took the oath. Overall, our results indicate that integrity oaths for executives improve firms’ financial reporting quality. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: M40; M41.